THE ROLE OF METABOLIC SYNDROME IN THE DEVELOPMENT OF CHRONIC CEREBRAL ISCHEMIA AND OPTIMIZATION OF TREATMENT (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Chronic cerebral ischemia (CCI) is a progressive condition that impairs blood flow to the brain, leading to cognitive decline, neurological dysfunction, and an increased risk of stroke. Metabolic syndrome, characterized by a cluster of conditions such as hypertension, obesity, dyslipidemia, and insulin resistance, is a well-recognized risk factor for cardiovascular diseases. However, its role in the development and progression of CCI has garnered growing attention. Understanding the relationship between metabolic syndrome and CCI is critical for optimizing treatment strategies and improving patient outcomes.